Nilai Spiritualisme dalam Pancasila - Natya Amelya Yahya; Citra Syahrani; Usiono Usiono (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
Over the years, value has been an important part of philosophical discussions, both implicitly and directly. Spiritualism is a teaching that says that the soul is the absolute reality of nature in the universe, and that the soul is the basis of the universe and provides a rational explanation. The first principle of Pancasila, Belief in One God, shows the value of spiritualism in its foundation. The value of spiritualism in its general form can be seen in the articles of the 1945 Constitution, especially Article 29 of the Amended 1945 Constitution. Spirituality focuses on a way of life, rather than abstract and speculative philosophical formulations. "Spirituality" is also considered a way that can be used to bring a person to the desired life. Exploring the values of Pancasila as a Liberating Spirituality is an effort and commitment as citizens of the nation, state, and religious communities to make Pancasila a guiding spirit in carrying out the governance of personal and social life of the nation and state. The national spirit of Pancasila truly becomes an inclusive social virtue, inspiring, uniting, and liberating all social groups, ethnicities, religions, languages, and aspirations. The spiritual values contained in Pancasila are divinity, humanity, unity, deliberation, and justice. These values are aligned with the universal values of all religions. Taking Pancasila as a liberating spirituality can help integrate the diversity-also known as kebhinekaan-that characterizes Indonesia around the world. In the face of the COVID-19 pandemic, the national spirit and liberating spirituality of Pancasila values are essential to anticipate and deal with such a crisis. The incarnation of the spirit of Pancasila can be seen in the benefits of national life, such as harmony, tolerance, solidarity, compassion, gotong royong, equality of the dignity of every Indonesian before the law, freedom of expression responsibly, and social solidarity. The sense of nationality reminds us how important it is for every Indonesian son and daughter to stick to the basic principles of national life, namely the love of the homeland, language, and one nation, Indonesia. Loyalty is not limited to religion, culture or geographical region. Basic human values can serve as benchmarks for a country's political, legal and economic systems, so that the spiritual values of Pancasila can liberate and liberate every citizen.